Education and personalized genomics: deciphering the public's genetic health report - Lamb, Neil E (2009)
Where do members of the public turn to understand what genetic tests mean in terms of their own health? Now that genome-wide association studies and complete genome sequencing are widely available, the importance of education in personalized genomics cannot be overstated. Although some media have introduced the concept of genetic testing to better understand health and disease, the public's understanding of the scope and impact of genetic variation has not kept up with the pace of the science or technology. Unfortunately, the likely sources to which the public turn to for guidance – their physician and the media – are often no better prepared. We examine several venues for information, including print and online guides for both lay and health-oriented audiences, and summarize selected resources in multiple formats. We also note on the roadblocks to progress and discuss ways to remove them, as urgent action is needed to connect people with their genomes in a meaningful way.